Discussing The Anatomy Table and The Vaccination Picture - Caulfield, Sean; Caulfield, Timothy; Holst, Johan (Imaginations)

(untitled) (York University, 2020)
The Anatomy Table is a print-based work that thematically addresses the loss of public trust in science, as well as misinformation surrounding science-informed interventions in health care, such as vaccination. Drawing on the history of anatomical illustration by referencing Andrea Vesalius’s famous 16th-century anatomical book, On the Fabric of the Human Body, the work combines this with contemporary drawings that suggest anatomy but which have an imagined, nonsensical quality, indicating to viewers that the drawings are not accurate representations of human anatomy. In addition to reflecting on this piece and the process of collaboration, Caulfield, Caulfield, and Holst discuss the challenge of countering misinformation in healthcare today. The work was created through collaborative dialogue between Sean Caulfield, a professor in the Department of Art and Design at the University of Alberta, Timothy Caulfield, Canada Research Chair in Health Law and Policy at the University of Alberta, and Johan Holst, senior scientist previously working at the Norwegian Institute of Public Health in Oslo and from August 2016 being a vaccine expert at the Headquarter of CEPI (Coalition for Epidemic Preparedness Innovations), situated in Oslo, Norway.